Development of the two forms of social anxiety in adolescence - Melita Puklek Levpušček (Psihološka Obzorja, 2004)
In the last decade studies of social anxiety have focused on research of social anxiety in childhood and adolescence. They showed that social anxiety was related to negative self-perceptions and lower social adaptation. The research question not yet answered considers the developmental trend of social anxiety in various periods of adolescence. In the study we proposed that at least social anxiety in its cognitive form (i.e., worries and fear of negative social evaluation) would decrease from early to late adolescence. We were also interested in personal characteristics that predict prolongation of social anxiety in late adolescence. The initial sample consisted of 325 early, middle and late adolescents to whom measures of social anxiety, self-consciousness and self-perceptions were administered. Two well-known aspects of social anxiety were measured: fear of negative social evaluation and social tension and inhibition. Early and middle adolescents were retested two years later at their transition to middle and late adolescence, respectively. Results from the first and the second assessment indicated that late adolescence is a time when the cognitive form of social anxiety in both adolescent males and females decreased. Social tension and inhibition showed a decrease only in adolescent females. Adolescent females reported more fear of negative social evaluation than males. Lower appraisal of one's own global and social competence and prolonged self-preoccupations were identified as characteristics of socially anxious late adolescents.